Analisis Forensik Kasus Penipuan Berkedok Investasi Doni Salmanan Pada Platform Quotex - Izza Amalia, Na’ Imatul; Mixghan Norman Antono (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The rapid development of science and technology has led to the emergence of various crimes that violate the law by utilizing technology, for example the Doni Salmanan binary option fraud case, which uses the quotex and flexing platforms on social media to influence the public so that they are interested in trading. This relates to forensic linguistics which analyzes the relationship between language and the field of law. This study aims to 1) understand the utterances used by Doni Salmanan to influence someone from a pragmatic perspective of speech acts, 2) understand the meaning of the language used by Doni Salmanan from a semantic perspective, 3) examine how the relationship between the language used by Doni Salmanan and violations in the world of law . The method used in this study is a qualitative method, data collection techniques in the form of documentary studies, and using a forensic linguistic approach from the pragmatic and semantic perspectives of speech acts. The results of this study concluded that Doni deliberately spread hoax news, flexing and charity with the aim of convincing and motivating members that his current wealth is the result of trading. From a pragmatic point of view, the speech delivered by Doni Salmanan contains illocutionary and perlocutionary meanings. Meanwhile, from a semantic point of view, it can be concluded that binary options trading does not have a definite profit and the teaching method may not be profitable because the activity is chancy. So that Doni violated Article 45A paragraph (1) in conjunction with Article 28 paragraph (1) RI Law number 11 of 2008 concerning ITE as amended and added to RI Law number 19 of 2016 concerning ITE. Then article Article 378 of the Criminal Code concerning Fraud and Article 3 of the Republic of Indonesia Law number 8 of 2010 concerning the Crime of Money Laundering (TPPU)